PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA - Prastiti, Anindyah; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2013)
This research aims to obtain empirical evidence about the role of board of commissioners (BOC) and audit committees on earnings management. The examined variables in this research are consisting of independent, dependent and control variables. The independent variables tested in this research consisted of the characteristics of BOC (size, independency, financial expertise, and meetings) and the characteristics of audit committees (size, independency, financial expertise, and meetings). While, the dependent variable is earnings management which is measured by discretionary accrual estimated by using Jones modified model. Last, the control variables are firm’s size measured by using the natural logarithm of total assets and leverage measured by the ratio of total debt to total assets.This research uses data of 244 manufacturing companies listed in IDX from 2009 until 2011. The sampling method used in this research is purposive sampling method. Data of BOC and audit committees were collected from annual report. The data then analized using multiple regression analysis.The results of this research showed that the size of BOC, independency of BOC, and independency of audit commitees have significant negative effect on earnings management. The other characteristics of BOC and audit commitees have no significant effect on earnings management. However, firm’s size and leverage as control variables have positive effect on earnings management.